Role of Asphericity in Choice of IOLs for Cataract Surgery - Aman Khanna; Rebika Dhiman; Rajinder Khanna; Yajuvendra Singh Rathore; Spriha Arun (Delhi Journal of Ophthalmology)
Advances in surgical techniques, as well as the invention of new intraocular lens (IOL) materials and designs, have increased expectations from cataract surgery to beyond simply providing good visual acuity. The cornea itself induces some degree of positive spherical aberration which is compensated by the negative spherical aberration of the clear crystalline lens. However, this compensation gradually decreases as the crystalline lens ages and particularly after cataract extraction and intraocular lens implantation. Conventional spherical IOLs add positive spherical aberration to the pre-existing aberrations caused by the cornea, increasing the total spherical aberration of the eye. One key factor contributing to postoperative spherical aberration is IOL design which has undergone dramatic changes to compensate for the positive corneal spherical aberration, with the emergence of aspheric IOL’s it has become a challenging task for ophthalmologists to choose the appropriate IOL from a wide variety available. This review article will provide information regarding asphericity and different aspheric IOL’s available and application of different strategies while choosing specific IOL.